Improving complementary feeding in Ghana: reaching the vulnerable through innovative business—the case of KOKO Plus. (16th December 2014) - Ghosh, Shibani; Tano‐Debrah, Kwaku; Aaron, Grant J.; Otoo, Gloria; Strutt, Nicholas; Bomfeh, Kennedy; Kitamura, Satoshi; Suri, Devika J.; Murakami, Hitoshi; Furuta, Chie; Sarpong, Daniel; Saalia, F.; et al.
Abstract : Reaching vulnerable populations in low‐resource settings with effective business solutions is critical, given the global nature of food and nutrition security. Over a third of deaths of children under 5 years of age are directly or indirectly caused by undernutrition. The Lancet series on malnutrition (2013) estimates that over 220, 000 lives of children under 5 years of age can be saved through the implementation of an infant and young child feeding and care package. A unique project being undertaken in Ghana aims to bring in two elements of innovation in infant and young child feeding. The first involves a public–private partnership (PPP) to develop and test the efficacy and effectiveness of the delivery of a low‐cost complementary food supplement in Ghana called KOKO Plus™. The second involves the testing of the concepts of social entrepreneurship and social business models in the distribution and delivery of the product. This paper shares information on the ongoing activities in the testing of concepts of PPPs, social business, social marketing, and demand creation using different delivery platforms to achieve optimal nutrition in Ghanaian infants and young children in the first 2 years of life. It also focuses on outlining the concept of using PPP and base‐of‐the‐pyramid approaches toward achieving nutrition objectives.